Bentuk Hias Tembikar Di Wilayah Sumbagsel: Kunduran, Lolo Gedang, dan Muak Ornamental Shape Pottery In The Southern Sumatera Region: Lolo Gedang, Muak, and Kunduran - Prasetiyo, Muhamad Hadi; Purwanti, Retno (Balai Arkeologi Sumatera Selatan, 2017)
Abstract. Pottery is a tool made by hands with special skills. Pottery one of the cultural results that began to be known at the time of cultivation in Indonesia. Pottery is a fragile item, because the ingredients and the manufacturing process produce goods that have limited endurance in their use. The varying needs of pottery also indicate the diversity of forms made of produced. Pottery artifacts are often found on archaological sites, either intact or broken in an occasional amount, and are the most dominant artifact findings among other artefact findings. From pottery data may be revealed some aspects of human life supporters, both the maker and the wearer. Research that has been done by archaeology center of south sumatera and the center of national archaeology research and development in sumbagsel region found many decorative pottery such as Kunduran Site, Lolo Gedang, and Muak. From Kunduran 9 decorative pottery, Lolo Gedang 41 decorated pottery, and Muak 11 decorated pottery.